Exploring Marginalisation: An Overview of Racism: The Evolution and Impact of Racism in Society (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Race is primarily a factor which is natural unlike gender or class. The factors that classify one as belonging to a particular race are required at the time of birth. Race is defined on the basis of colour of skin and physical features like hair, lips or the size of skull and so on. One cannot acquire a race. One is born to a race. Thus race is something permanent. So racial identity is something fixed and that cannot be overcome. The present paper focuses on the different approaches to race, tracing the evolution of racism. The study also explores how this racial politics operates at micro levels in the society.